Checklist of the butterflies (Lepidoptera: Papilionoidea) of Montenegro - Franeta, Filip (Zootaxa, 2018)
Montenegro is, from an entomological point of view, one of the least studied countries in Europe. The Lepidoptera order has been severely understudied and an updated butterfly checklist has not been published for more than 30 years. Without proper knowledge on the species composition, and their distribution throughout the country, appropriate conservation measures cannot be undertaken. Thus an updated checklist of the butterflies of Montenegro was urgently needed. In this paper a list of 192 species of butterflies is presented, based on all available literature and on the authors’ own data gathered from 1998 to 2017. The inclusion or omission of some species from the list, as well as the occurrence and distribution of rare species, is discussed. A short historic overview of entomological research in Montenegro is also included. Records of five species, Lycaena thersamon, Kretania sephirus, Neptis sappho, Arethusana arethusa, and Erebia alberganus, discovered for the first time in the country, are presented.